Competencies needs of secondary school teachers for implementation of entrepreneurial business trades curriculum in Adamawa State, Nigeria - Dhalum, N. Cigar; Adamu, Ibrahim; Muhammad, Adam (Kashere Journal of Education, 2023)
The study investigated “Competencies Needs of Secondary Schools Teachers for Implementation of Entrepreneurial Business Trades Curriculum in Adamawa State, Nigeria”. As a guide, two specific objectives, research questions and null hypotheses were raised. Descriptive survey was used for the study. The population of the study was 220 business trade teachers in Adamawa State secondary schools, and Total Population Sample (TPS) was used for the study. A 4-point scale structured questionnaire was used for data collection. The instrument was validated by four experts and pilot study was carried out in Gombe State senior secondary schools to test the validity of the instrument using Cronbach Alpha reliability test which yielded a coefficient of .846. Statistical Package of Social Science (SPSS), 25 was used to process the mean scores and standard deviations for answering the research questions, while the hypotheses were tested using Analysis of Variance at 0.05 level of significant. The study disclosed that Business Trades teachers need competencies in entrepreneurial skills competencies and basic competencies for effective implementation of Entrepreneurial Trade subjects in secondary schools, without which the objectives of the curriculum would not be achieved. The study concluded that, the introduction of Entrepreneurial Business Trade subjects at the secondary school level will not address the problem of unemployment if the situation of the teachers who are responsible for the implementation of the curriculum remained unchanged. Based on these, it was recommended among others that government should organize training sessions for business trade subject teachers, to enable them to acquire the needed competencies for instructional delivery in the secondary schools. It was suggested that Entrepreneurial Business Trade teachers should acquire the two competencies entrepreneurial skills and basic competencies for implementation of entrepreneurial business trades curriculum in the secondary schools, so as to achieve the desired objectives for which the curriculum was developed, that is self-employment, self-reliance and sustenance in all facets of economic, social, political and technological developments.